Pressure-induced isostructural phase transformation in γ-B28 - Zarechnaya, Evgeniya; Dubrovinskaia, Natalia; Caracas, Razvan; Merlini, Marco; Hanfland, Michael; Filinchuk, Yaroslav; Chernyshov, Dmitry; Dmitriev, Vladimir; Dubrovinsky, Leonid (Physical review. B, Condensed matter and materials physics, 2010)
Isostructural phase transformations (ISPhTs) so far were reported only for heavy elements and their compounds with complex electronic and/or magnetic structures. Studies of one of the lightest elemental material, high-pressure boron γ-B28, by means of in situ single-crystal x-ray diffraction and Raman spectroscopy reveal abrupt changes in the compressional behavior and Raman spectra at 40 GPa. Combined experimental and ab initio theoretical analysis of the structural and vibrational properties of γ-B28 suggests that the ISPhT under compression is due to the changes in the polarity of the covalent bonds between the boron atoms in the complex quasimolecular structure of γ-B28.
Published 18 November 2010
Die 28 im Titel ist tiefgestellt
Gesehen am 17.04.2024